2022
DOI: 10.4041/kjod21.180
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment of anterior open bites using non-extraction clear aligner therapy in adult patients

Abstract: Objective The purpose of this study was to examine the effectiveness and mechanism of clear aligner therapy for the correction of anterior open bite in adult nonextraction cases. Methods Sixty-nine adult patients with anterior open bite were enrolled and classified into Angle’s Class I, II, and III groups. Fifty patients presented with skeletal open bite (mandibular plane angle [MPA] ≥ 38°), whereas 19 presented with dental open bite. Fifteen cephalometric landmarks wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 31 publications
1
23
0
1
Order By: Relevance
“…According to the bone density classification, the bone in the posterior region of the maxilla is often of D4 type, which represents fine trabecular bone; whereas, In the posterior mandible, the bone is of type D3 or in some cases D2, which indicates porous cortical bone [ 19 ]. In agreement with our finding, Suh et al [ 20 ] as well did not observed significant intrusions in the posterior mandible, even despite planning for lower molar intrusion for 0.5 to 0.6 mm. However, Moshiri et al [ 21 ] stated that aligners cannot intrude posterior teeth without any planned design.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…According to the bone density classification, the bone in the posterior region of the maxilla is often of D4 type, which represents fine trabecular bone; whereas, In the posterior mandible, the bone is of type D3 or in some cases D2, which indicates porous cortical bone [ 19 ]. In agreement with our finding, Suh et al [ 20 ] as well did not observed significant intrusions in the posterior mandible, even despite planning for lower molar intrusion for 0.5 to 0.6 mm. However, Moshiri et al [ 21 ] stated that aligners cannot intrude posterior teeth without any planned design.…”
Section: Discussionsupporting
confidence: 94%
“…In the study of Talens-Cogollos et al [ 3 ], no significant changes in the mandibular plane were observed in any of the patients at the end of the treatment, which was attributed to the small amount of posterior intrusion. Suh et al [ 20 ] as well reported no significant changes in the vertical dimension, which can be related to the high number of hyperdivergent patients in their study. In other words, it might be said that clear aligners control the vertical dimension of the face rather than reducing it [ 20 ].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Additional intermaxillary elastics or optimized attachments are not necessary for these maneuvers. According to the literature on anterior open bites treated using clear aligners, most of them suggest that the bite closure is achieved by a combination of maxillary and mandibular incisor extrusion along with maxillary and mandibular molar intrusion leading to a slight reduction in the mandibular plane angle 18‐21 . (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Orthodontic correction of anterior open bite in patients with hyperdivergent skeletal pattern was previously considered challenging, as the vertical problems usually combine with the transverse and sagittal problems, and the overall correction is prone to relapse. 1 Even though few cases with anterior open bite have been treated by extruding incisors using various methods, 2 intrusion of maxillary molars is required to promote the counterclockwise rotation of the mandible, which results in a decrease of the anterior facial height and advancement of the retruded chin. Moreover, in a recent systematic review and meta-analysis, it was concluded that the stability of anterior open bite treatment with molar intrusion was similar to the stability after surgical approaches.…”
Section: Introductionmentioning
confidence: 99%